Pelatihan Teknik Dasar Tenis Meja pada Siswa SD 119 Belalang di Kelurahan Mataran - Rita Erawati; Andi Ogo Darminto; Alif Aryadi Hardi; Maria Herlinda Dos Santos; Khalid Rijaluddin; Rahmat Ilahi; Andi Temmassonge; Andi Wirawan Risal; A. Mutmainna (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Table tennis is a sport that is often played by many people because it is an easy and interesting sport to play and is also a sport that is popular with many people, not only teenagers, but also elderly people, both men and women. But many players also don't know and understand the basic techniques of table tennis. The aim of this training is to provide knowledge and insight into basic table tennis techniques to students at SD 119 Belalang in Mataran Village. The problems found in elementary school 119 Grasshopper students did not master the basic techniques in playing table tennis. The method used in this service is the training method. The participants in this basic engineering training were 16 students from SD 119 Belalang. The result of implementing this training is that students can demonstrate increased knowledge and skills in performing basic table tennis techniques including basic techniques of serving, bet grip, smash, backhand and forehand strokes so that this training makes SDGs point 4 namely quality education implemented.